2011
DOI: 10.5433/1679-0367.2011v32n1p69
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade e similaridade entre populações de insetos aquáticos em riachos de primeira e segunda ordem, sul do Brasil

Abstract: ResumoA estrutura das comunidades de macroinvertebrados aquáticos é influenciada pela velocidade da correnteza do curso d'água e da heterogeneidade de habitats entre outras características. Este trabalho verificou a relação da diversidade de insetos aquáticos com a ordem hidrológica de dois riachos. Para isso, foi testada a seguinte hipótese: a diversidade de insetos associados ao mesmo substrato em trechos equivalentes de riachos classificados em diferentes ordens é semelhante. Amostras de folhiço foram colet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…We sampled a total of 569 individuals, distributed into 27 families (class, for Hirudinea) comprised of 9 orders (Table 1). The taxa with the highest values of total abundance were Aeglidae at points 2 and 3, followed by Leptoplhebiidae (Ephemeroptera), corroborating data from Santestevan (2004) and Raio et al (2011), who observed this family as one of the most abundant in Paraná State watercourses. The construction of such knowledge is fundamental since the lack of consistent knowledge regarding aquatic invertebrates of watercourses in Paraná state (mainly low-order rivers in small municipalities, see Crisigiovanni et al, 2020) is an impediment to further applied researches, such as preventing data use in an important and large-scale analysis like the one performed by Dala-Corte et al (2020).…”
Section: Resultssupporting
confidence: 86%
“…We sampled a total of 569 individuals, distributed into 27 families (class, for Hirudinea) comprised of 9 orders (Table 1). The taxa with the highest values of total abundance were Aeglidae at points 2 and 3, followed by Leptoplhebiidae (Ephemeroptera), corroborating data from Santestevan (2004) and Raio et al (2011), who observed this family as one of the most abundant in Paraná State watercourses. The construction of such knowledge is fundamental since the lack of consistent knowledge regarding aquatic invertebrates of watercourses in Paraná state (mainly low-order rivers in small municipalities, see Crisigiovanni et al, 2020) is an impediment to further applied researches, such as preventing data use in an important and large-scale analysis like the one performed by Dala-Corte et al (2020).…”
Section: Resultssupporting
confidence: 86%
“…Several studies have shown the wide distribution of immature Odonata in streams where the composition and distribution of these insects are influenced by the interaction among physical, chemical, structural and hydrological variables (Gibbs et al, 2004;Maltchik et al, 2010;Raio et al, 2011;Che Salmah et al, 2012;Gómez-Anaya et al, 2013). Thereby, changes in the water body characteristics can strongly influence the spatial and temporal distribution patterns of the odonatofauna (Buss et al, 2002(Buss et al, , 2004Silveira et al, 2007).…”
mentioning
confidence: 99%